Forensic science and student mobility programs in the Indo-Pacific region: Unveiling the potential of an international and intercultural project in forensic science education (Journal of Applied Learning and Teaching, 2019)
Forensic science is the application of science in a criminal investigation or court of law. Crimes and forensic investigation have always been associated with human society. As an interdisciplinary field, forensic science incorporates areas of both life sciences and social sciences. Until the beginning of the 1900s, forensic science was self-taught and carried out exclusively through law enforcement agencies. In recent years, with the success of crime drama television series, an increased global interest in forensic science-based university courses has been observed. The prevalence of global issues such as international crimes and mass disasters has catalysed the need for international collaboration and to remove global barriers within forensic science. To prepare students for the world of work, it is pivotal that forensic science curricula address the needs of the present-day society and the requirements of the forensic providers (laboratories and law enforcement agencies). The present manuscript describes the first forensic science international curriculum between Australia (Murdoch University) and Malaysia (Universiti Kebangsaan Malaysia/UKM Forensics), possible through the New Colombo Plan of the Australian Government. The course outlined here, comprehensively comprised of lectures, workshops and mixed group crime scene simulations, provided Australian and Malaysian students with an authentic, intercultural and cross-jurisdictional learning experience to acquire work-ready skills.